Role of perception and motor programme in deliberate mirror writing - Yin-Wen, Kuo (The University of Edinburgh, 2011)
This study investigated the case who had been doing deliberate mirror writing for a long time. And hope to have an insight to the underlying mechanisms. The perceptual hypothesis and motor programme hypothesis were tested with four experiments. The results of mental rotation task of alphanumeric characters showed that KB had no difference in reaction times between forward characters conditions and backward characters conditions while control group needed longer time to respond to backward characters. Moreover, in the task of mental rotation of body parts, KB had a significant lower accuracy in hand condition, and fitted the criteria of dissociation between hand and foot conditions. It was suggested that KB’s deliberate mirror writing was related to both motor and perceptual processing.
The role of perception and motor programme in deliberate mirror writing
Keywords: mirror writing; mental rotation